2010
DOI: 10.1186/1471-2407-10-10
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensitization of cancer cells by siRNA using targeted nanogel delivery

Abstract: BackgroundChemoresistance is a major obstacle in cancer treatment. Targeted therapies that enhance cancer cell sensitivity to chemotherapeutic agents have the potential to increase drug efficacy while reducing toxic effects on untargeted cells. Targeted cancer therapy by RNA interference (RNAi) is a relatively new approach that can be used to reversibly silence genes in vivo by selectively targeting genes such as the epidermal growth factor receptor (EGFR), which has been shown to increase the sensitivity of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
120
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(123 citation statements)
references
References 45 publications
2
120
0
1
Order By: Relevance
“…Previous studies have shown that sensitizing cancer cells to chemotherapeutic agents can reduce the side effects as well as balance the efficacy and toxicity of chemotherapy [30]. Molecular pathways driving cancer progression or essential for the cancer cell survival could be targeted to sensitize the cells for chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that sensitizing cancer cells to chemotherapeutic agents can reduce the side effects as well as balance the efficacy and toxicity of chemotherapy [30]. Molecular pathways driving cancer progression or essential for the cancer cell survival could be targeted to sensitize the cells for chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Nanogels are able to be loaded with siRNA via "breathing-in" manner besides electrostatic attraction [94]. Dickerson et al [95] investigated core/shell nanogels composed of poly (N-isopropylmethacrylamide) (pNIPMAm) cross-linked with N,N′-methylene(bisacrylamide) to deliver siRNA targeting epidermal growth factor receptor (EGFR). Knockdown of (EGFR) contributes to the overcoming of MDR in cancer cells [96].…”
Section: Other Nanocarriersmentioning
confidence: 99%
“…It is also suggested a possible therapeutic effect of direct introduction of siRNA to CD44 into some human solid tumors with high expression of the CD44 gene [146]. Although the role of epidermal growth factor receptor (EGFR) in altering tumor chemosensitivity has not yet been fully elucidated, selectively targeting EGFR supplies the reversal possibility of chemoresistance in many tumor types [147]. Reduction of EGFR expression and increased chemosensitivity to docetaxel are emerging an effective strategy for the sensitization of cancer cells to taxane chemotherapy [147].…”
Section: Cancermentioning
confidence: 99%
“…Although the role of epidermal growth factor receptor (EGFR) in altering tumor chemosensitivity has not yet been fully elucidated, selectively targeting EGFR supplies the reversal possibility of chemoresistance in many tumor types [147]. Reduction of EGFR expression and increased chemosensitivity to docetaxel are emerging an effective strategy for the sensitization of cancer cells to taxane chemotherapy [147]. siRNA-PG-Amine polyplexes can be systemically delivered to tumors in mice [148], and siRNA-nanocarrier system can efficiently inhibit expression of a specific gene in tumor cells.…”
Section: Cancermentioning
confidence: 99%